2018
DOI: 10.1002/joa3.12134
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of cardiac resynchronization therapy in patients with heart failure in the Northern Region of New Zealand

Abstract: BackgroundCardiac resynchronization therapy (CRT) has been shown to improve morbidity and mortality for heart failure (HF) patients. Little is known about the trends in CRT use and outcomes of these patients in New Zealand.MethodMortality, hospitalization events and complications in HF patients in the Northern Region of New Zealand implanted with CRT devices from Jan‐2007 to June‐2015 were reviewed.ResultsTwo‐hundred patients underwent CRT implantation during the study period. There was a gradual increase in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This was a single-centre, retrospective observational study with relatively low sample size. We have recently published trends of CRT therapy use for eligible patients with HF in New Zealand and the data suggests that there is a significant unmet clinical need for CRT implantation in the Northern Region 30. Affordability and capacity are of concern in this region.…”
Section: Discussionmentioning
confidence: 99%
“…This was a single-centre, retrospective observational study with relatively low sample size. We have recently published trends of CRT therapy use for eligible patients with HF in New Zealand and the data suggests that there is a significant unmet clinical need for CRT implantation in the Northern Region 30. Affordability and capacity are of concern in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic heart failure (CHF) is the ultimate outcome of different cardiovascular diseases, which represents a public health problem requiring urgent attention all over the world due to its high morbidity, mortality, and rehospitalization rates [ 1 , 2 ]. The 2018 China Cardiovascular Diseases Report indicated that the number of patients with cardiovascular disease exceeded 200 million, and patients with heart failure accounted for 2%.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies in European countries have shown that the utilization rate of CRT for eligible CHF patients was only approximately 30%. 8, 9 In Japan, although the number of CHF patients has been increasing, as in the Western countries, 10,11 there has been no change in the number of new implantations or replacements of CRT. 12 In Japan, limited data are available on CRT utilization and long-term D evice therapy, including implantable cardioverter defibrillator (ICD) and cardiac resynchronization therapy (CRT), has been shown to improve morbidity and mortality in patients with heart failure with reduced ejection fraction (HFrEF).…”
mentioning
confidence: 99%